A bi-layer orientated and functionalized graphene-based composite coating with unique hydrogen gas barrier and long-term anti-corrosion performance. (5th March 2023) - Yuan, Sicheng; Sun, Yue; Cong, Chang; Liu, Yaran; Lin, Dan; Pei, Luchao; Zhu, Yanji; Wang, Huaiyuan
Abstract: Conventional hydrogen gas barrier composite coatings were facing low corrosion resistance and adhesion level issues, both of which could lead to high risks of hydrogen-related equipment failure. Herein, a unique bi-layer composite coating consisting of primer thermoplastic polyurethane (TPU) layer and top phenylenediamine (PPD) non-covalent modified orientated graphene (Gr-PPD) incorporated epoxy resin layer was prepared by a two-step high-speed spinning method. Orientated Gr-PPD due to high shearing force during spinning procedure and improved interfacial bonding between polymer and inorganic phases by amino groups interactions with EP during curing reaction created effective barriers and reduced free volume spaces in EP, beneficial for preventing the diffusion of hydrogen gas and corrosive media. In addition, surface dangling bonds existed on surface of Gr-PPD could position hydrogen atoms by C–H sp 3 bond, reducing the hydrogen permeation as well. The primer TPU coating was another protective layer to hinder hydrogen permeation and Gr conductive network formation. The |Z|0.01Hz value of optimum sample maintained 3.72 × 10 11  Ω cm 2 for 90-day immersion in 3.5 wt% NaCl solution and tolerated 60d incessant salt-spray attack. Plus, it showed 82.9% decrease in H2 permeability coefficient and high adhesion strength of 11.5 MPa, which presented high applicability in industrial environment. Graphical abstract: The prepared bi-layer composite coating exhibited unique hydrogen gas barrier, long-term corrosion resistance and enhanced adhesion strength. Image 1 Highlights: Orientated and functionalized graphene is achieved by high-speed spin coating and chemical modification. A unique bi-layer Gr-PPD-EP/TPU composite coating was elaborately designed. The dangling bonds on Gr could position hydrogen by C–H sp 3 bond. The composite coating exhibited excellent long-term anti-corrosion and improved hydrogen gas barrier performances.